Hubungan Tiongkok dan ASEAN: Upaya Tiongkok menjadi Kekuatan Hegemon di Asia Tenggara - Raihan Alfi; Fakhri Sabiq Muawal; Galih Arjuna Ismail (TRANSBORDERS: International Relations Journal, 2023)
China has turned into one of the most powerful countries in the world or "Great Powers" which has a vision to become a hegemonic country. Southeast Asia as China's backyard was the beginning of China's expansion to the world. China-ASEAN relations are very important because ASEAN is a strategic partner of China in trade cooperation. ASEAN can be a profitable companion for China in spreading its influence to the world. However, it is not that easy for ASEAN to support and assist China in achieving it. China spreads its influence through political, economic, socio-cultural and military aspects. In each of these aspects, China has a clear and measured strategy to implement it in order to achieve hegemony in Southeast Asia. The growth and rising of China into a great power is a testament to the massive effort made by China. This study analyzes the China-ASEAN relations in the efforts made by China with ASEAN. The author uses qualitative research methods with literature study to obtain various sources about China-ASEAN relations. It is undeniable that slowly China has become a new hegemon. This is evidenced by the massive influence of China in all aspects, especially the economy and military, which will slowly change the status quo in the international system.